A survey of canning practices of food plants in Manila and suburbs - Bernardo, Maria Aurora M.; Guzman, Matilde P. (1965., 1965)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Canned foods industry -- Philippines